Stepping left : dance and politics in New York City, 1928-1942 - Graff, Ellen (Duke University Press, 1997)
Stepping Left simultaneously unveils the radical roots of modern dance and recalls the excitement and energy of New York City in the 1930s. Ellen Graff explores the relationship between the modern dance movement and leftist political activism in this period, describing the moment in American dance history when the revolutionary fervor of "dancing modern" was joined with the revolutionary vision promised by the Soviet Union. This account reveals the major contribution of Communist and left-wing politics to modern dance during its formative years in New York City